Correction to: Blooming Plant and Bee Communities in an Inland Pacific Northwestern Forest Vary by Forest Type, Season, and Environmental Factors - Scott R. Mitchell; Sandra J. DeBano; Mary M. Rowland; Skyler Burrows; Ryan Nielson (Journal of Forestry, 2026)

The potential to improve hygiene standards and eating quality of local beef in Eastern Indonesia - Naufal Armanditya; Dahlanuddin; Sukirno; Dedi Supriadi; Ryan Aryadin Putra; Fuji Astuti; Yusuf A. Sutaryono; Tanda S. Panjaitan; Peter McGilchrist; Renato Villano; Heather Burrow (Food and Humanity, 2026)

Blooming Plant and Bee Communities in an Inland Pacific Northwestern Forest Vary by Forest Type, Season, and Environmental Factors - Scott R. Mitchell; Sandra J. DeBano; Mary M. Rowland; Skyler Burrows; Ryan Nielson (Journal of Forestry, 2026)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Factors affecting broadscale variation in nearshore water-column organic carbon concentrations along the Great Barrier Reef - Ryan M. Burrows; Alexandra Garzon-Garcia; Joanne Burton; Stephen E. Lewis; Renee K. Gruber; Jon E. Brodie; Michele A. Burford (Regional Studies in Marine Science, 2023)

Resolving the Drivers of Algal Nutrient Limitation from Boreal to Arctic Lakes and Streams - Maria Myrstener; Megan L. Fork; Ann-Kristin Bergström; Isolde Callisto Puts; Demian Hauptmann; Peter D. F. Isles; Ryan M. Burrows; Ryan A. Sponseller (Ecosystems, 2022)
Nutrient inputs to northern freshwaters are changing, potentially altering aquatic ecosystem functioning through effects on primary producers. Yet, while primary producer growth is sensitive to nutrient supply, it is also constrained by a suite of other factors, including light and temperature, which may play varying roles across stream and lake habitats. Here, we use bioassay results from 89 lakes and streams spanning northern boreal to Arctic Sweden to test for differences in nutrient limitation status of algal biomass along gradients in colored dissolved organic carbon (DOC), water temperature, and nutrient concentrations, and to ask whether there are distinct patterns and drivers between habitats. Single nitrogen (N) limitation or primary N-limitation with secondary phosphorus (P) limitation of algal biomass was the most common condition for streams and lakes. Average response to N-addition was a doubling in biomass; however, the degree of limitation was modulated by the distinct physical and chemical conditions in lakes versus streams and across boreal to Arctic regions. Overall, algal responses to N-addition were strongest at sites with low background concentrations of dissolved inorganic N. Low temperatures constrained biomass responses to added nutrients in lakes but had weaker effects on responses in streams. Further, DOC mediated the response of algal biomass to nutrient addition differently among lakes and streams. Stream responses were dampened at higher DOC, whereas lake responses to nutrient addition increased from low to moderate DOC but were depressed at high DOC. Our results suggest that future changes in nutrient availability, particularly N, will exert strong effects on the trophic state of northern freshwaters. However, we highlight important differences in the physical and chemical factors that shape algal responses to nutrient availability in different parts of aquatic networks, which will ultimately affect the integrated response of northern aquatic systems to ongoing environmental changes.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Water velocity and groundwater upwelling influence benthic algal biomass in a sandy tropical river: implications for water-resource development - Ryan M. Burrows; Leah Beesley; Michael M. Douglas; Bradley J. Pusey; Mark J. Kennard (Hydrobiologia, 2020)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Persistent nitrogen limitation of stream biofilm communities along climate gradients in the Arctic - Maria Myrstener; Gerard Rocher‐Ros; Ryan M. Burrows; Ann‐Kristin Bergström; Reiner Giesler; Ryan A. Sponseller (Global Change Biology, 2018)
Climate change is rapidly reshaping Arctic landscapes through shifts in vegetation cover and productivity, soil resource mobilization, and hydrological regimes. The implications of these changes for stream ecosystems and food webs is unclear and will depend largely on microbial biofilm responses to concurrent shifts in temperature, light, and resource supply from land. To study those responses, we used nutrient diffusing substrates to manipulate resource supply to biofilm communities along regional gradients in stream temperature, riparian shading, and dissolved organic carbon (DOC) loading in Arctic Sweden. We found strong nitrogen (N) limitation across this gradient for gross primary production, community respiration and chlorophyll‐ a accumulation. For unamended biofilms, activity and biomass accrual were not closely related to any single physical or chemical driver across this region. However, the magnitude of biofilm response to N addition was: in tundra streams, biofilm response was constrained by thermal regimes, whereas variation in light availability regulated this response in birch and coniferous forest streams. Furthermore, heterotrophic responses to experimental N addition increased across the region with greater stream water concentrations of DOC relative to inorganic N. Thus, future shifts in resource supply to these ecosystems are likely to interact with other concurrent environmental changes to regulate stream productivity. Indeed, our results suggest that in the absence of increased nutrient inputs, Arctic streams will be less sensitive to future changes in other habitat variables such as temperature and DOC loading.

Land use influences macroinvertebrate community composition in boreal headwaters through altered stream conditions - Micael Jonsson; Ryan M. Burrows; Johan Lidman; Emma Fältström; Hjalmar Laudon; Ryan A. Sponseller (Ambio, 2017)

Seasonal resource limitation of heterotrophic biofilms in boreal streams - Ryan M. Burrows; Hjalmar Laudon; Brendan G. McKie; Ryan A. Sponseller (Limnology and Oceanography, 2017)
Unraveling the potentially shifting controls over microbial activity among habitats and across seasonal transitions is critical for understanding how freshwater ecosystems influence broader elemental cycles, and how these systems may respond to global changes. We used nutrient‐diffusing substrates to investigate seasonal patterns and constraints on microbial activity of biofilms in streams draining distinct landscape features of the boreal biome (forests, mires, and lakes). Microbial respiration (MR) largely mirrored spatial and temporal variation in water temperature. However, limitation by labile carbon (C) was a constraint to microbial activity during ice‐covered periods, when MR of control nutrient‐diffusing substrates fell below rates predicted from stream temperature alone. Variation in C limitation among the study streams was reflective of putative organic C availability, with C limitation of biofilms weakest in the dissolved organic C (DOC)‐rich, mire‐outlet stream and greatest in the relatively DOC‐poor, forest stream. Incidences of nutrient limitation were only observed during warmer months. Our study illustrates how variation in processes mediated by heterotrophic biofilms and seasonal shifts in resource limitation can emerge in a stream network draining a heterogeneous landscape. In addition, our results show that, for a large portion of the year, heterotrophic processes in boreal streams can be strongly limited by the availability of labile C, despite high DOC concentrations. Metabolic constraints to dissolved organic matter processing at near‐freezing temperatures, coupled with hydrological controls over the delivery of more labile organic resources to streams (e.g., soil freezing and flooding), have potentially strong influences on the productivity of boreal streams.

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Biogenesis of P seudomonas aeruginosa type IV pili and regulation of their function - Tiffany L. Leighton; Ryan N. C. Buensuceso; P. Lynne Howell; Lori L. Burrows (Environmental Microbiology, 2015)
Summary Type IV pili ( T4P ) are bacterial virulence factors involved in a wide variety of functions including deoxyribonucleic acid uptake, surface attachment, biofilm formation and twitching motility. While T4P are common surface appendages, the systems that assemble them and the regulation of their function differ between species. Pseudomonas aeruginosa , N eisseria spp. and M yxococcus xanthus are common model systems used to study T4P biology. This review focuses on recent advances in P . aeruginosa T4P structural biology, and the regulatory pathways controlling T4P biogenesis and function.

Greater phosphorus uptake in forested headwater streams modified by clearfell forestry - Ryan M. Burrows; Jason B. Fellman; Regina H. Magierowski; Leon A. Barmuta (Hydrobiologia, 2013)